Buddhist Cultural Ecology - (Matcha Bunchai), Phrakhru Udomthamwat; Saññato, Phramaha Samrong; Saengsai, Prayoon (Journal of Graduate MCU KhonKaen Campus, 2022)
This paper aims to study the concept of cultural ecology. It is an anthropological concept that focus on the study of socio-cultural changes, emphasis on the influence of the environment as a factor in the process of cultural evolution. In Buddhism, what is known as necessities of Buddhist monks or followers are the environment, both natural and man –made, which affects human life and spiritual development. Ecology in Buddhism is divided into two types: 1) natural ecosystems, there is, non-living ecology, including physical laws and living natural systems, such as, biological laws and psychic law. 2) cultural ecology system. It consists of concrete and abstract cultural ecology. The integrated Buddhist cultural ecology model consists of 2 aspects: The external Theravada Buddhist cultural ecology according to the 7 Sappaya and the internal ecology based on the 4 Bhavana has two goals: the physical goal is factor of the four necessities of life and the mental goal is the 6 sense-impression to make human habitation a pleasant place to live.